1988
DOI: 10.2170/jjphysiol.38.839
|View full text |Cite
|
Sign up to set email alerts
|

Tetrodotoxin-unaffected depolarization of frog muscles induced by the venom of jellyfish (genus Aurelia).

Abstract: In the isolated frog muscle, the proteinaceous venom extracted from jellyfish (genus Aurelia) produced 1) a complete and irreversible block of indirectly and directly elicited muscle twitch and 2) an irreversible depolarization of the muscle membrane. This venom-induced depolarization was effectively reversed or prevented by the substitution of choline for sodium in Ringer solution, but not by the introduction of tetrodotoxin (TTX), a sodium channel blocker. The mechanism of muscle membrane depolarization appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Lanes 1-6 fishing tentacles of C. cap 1-5, lanes 6-10 oral arms of C. cap 1-5 vivo experiments whereby proteinaceous extracts from this medusa were administered to rabbits showed an induction of paralysis and glomerulonephritis (Wiersbitzky et al, 1973). A protein extract from whole A. aurita specimens caused muscle depolarization, indicating changes in sodium channel activity (Kihara et al, 1988). However, these two studies did not deal with causative toxins that may have been involved in the physiological observations.…”
Section: Discussionmentioning
confidence: 99%
“…Lanes 1-6 fishing tentacles of C. cap 1-5, lanes 6-10 oral arms of C. cap 1-5 vivo experiments whereby proteinaceous extracts from this medusa were administered to rabbits showed an induction of paralysis and glomerulonephritis (Wiersbitzky et al, 1973). A protein extract from whole A. aurita specimens caused muscle depolarization, indicating changes in sodium channel activity (Kihara et al, 1988). However, these two studies did not deal with causative toxins that may have been involved in the physiological observations.…”
Section: Discussionmentioning
confidence: 99%
“…The venom from Aurelia was shown to effect isolated frog muscle, as a complete and irreversible block of indirectly and directly elicited muscle twitches and an irreversible depolarization of the muscle membrane, probably caused by an increase in membrane permeability to sodium ions [111]. …”
Section: Cnidarian Jellyfish Venomsmentioning
confidence: 99%
“…However, significant envenomation has been described for its stings, characterized by local pain, intense itching, ulceration, and appearance of vesiculopapular erythematous eruptions [6,7]. A. aurita crude venom and partially purified fractions have been reported to produce hemolysis, cytotoxicity, dermonecrosis, lethality, neurotoxicity, and to contain phospholipase activity [7,8,9,10,11,12]. In particular, only a few studies have focused on characterizing A. aurita neurotoxins.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Segura-Puertas et al [7] reported some protein fractions that caused paralysis and death of crabs when tested in vivo . Likewise, Kihara and colleagues [10] demonstrated that a venom preparation caused depolarization of frog muscle membranes that was attributed mainly to sodium ion influx. A similar feature has been suggested for other scyphozoan jellyfish venoms that appear to induce the opening or activation of non-selective cationic channels and a subsequent increase of inward sodium-elicited currents [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%